Dengue Fever in Travelers to the Tropics, 1998 and 1999 - Heidi Lindbäck (Emerging Infectious Diseases, 2003)
Dengue fever (DF) has become common in western travelers to the tropics. To improve the basis for travel advice, risk factors and dengue manifestations were assessed in 107 Swedish patients for whom DF was diagnosed after return from travel in 1998 and 1999. Patient data were compared with data on a sample of all Swedish travelers to dengue-endemic countries in the same years. Only three of the patients had received pretravel advice concerning DF from their physicians. Hemorrhagic manifestations were common (21 of 74 patients) but caused no deaths. Risk factors for a DF diagnosis were travel to the Malay Peninsula (odds ratio [OR] 4.95; confidence interval [CI] 2.92 to 8.46), age 15–29 years (OR 3.03; CI 1.87 to 4.92), and travel duration >25 days (OR 8.75; CI 4.79 to 16.06). Pretravel advice should be given to all travelers to DF-endemic areas, but young persons traveling to southern and Southeast Asia for >3 weeks (who constituted 31% of the patients in our study) may be more likely to benefit by adhering to it.